Field evaluation of fungicides against leaf and fruit spot diseases of pomegranate (Punica granatum L.) (IASH Indian Journal of Arid Horticulture, 2026)
A two-year field experiment was conducted during Mrig Bahar to evaluate the efficacy of different fungicides against Anthracnose and Alternaria leaf and fruit spot diseases of pomegranate (Punica granatum L.). Three sprays were applied at 15-day intervals and disease observations on leaves and fruits were recorded 15 days after the final spray. Results revealed that the ready-mix fungicide Tebuconazole 50% + Trifloxystrobin 25% WG was found significantly effective treatment, recording the lowest PDI of 14.03% on leaves and 13.96% on fruits. Plants treated with Tebuconazole 50% + Trifloxystrobin 25% WG showed minimum yield loss.